Nurses’ Knowledge and Role in the Management of Thalassemic Patients in Sulaimania Thalassemia Center - azize, Pary; tahir, Farida; Kelsey, Janet (Iraqi National Journal of Nursing Specialties, 2015)
The aim of this study is to assess nurse’s knowledge and role in the management of thalassemic patients in the Sulaimania Thalassemia Centre. Methodology: This study utilized a qualitative approach to explore nurses’ knowledge about thalassemia through semi structured group interviews. Questionnaire was synthesized through a comprehensive review of literature. Results: The results show that nurses in Kurdistan region of Iraq have a limited role in terms of decision making and there is lack of nursing documentation other than that of recording abnormal events, and a lack of knowledge about and engagement in continuous training about the management of thalassemia and consider themselves not involved in initial or ongoing patient education; however they do have the role of explaining the risk of non-adherence to chelation drugs for the families. They consider themselves not supporting the patient’s psychological state. The knowledge of nurses with a university degree in Kurdistan regarding thalassemia is much better than the knowledge of a nurse without degree. There is however an overall lack of detailed knowledge of the genetics of thalassemia. Further studies should evaluate the role of the nurse in Kurdistan. Guidance and support for further education and training is required in order to enable nurses to fulfill their potential. Recommendations: Continuous education is necessary to facilitate the nurses to provide enhanced physical, psychological care besides the genetic enlightenment for the patients and their families.